SLC1A3 is a novel prognostic biomarker associated with immunity and EMT in hepatocellular carcinoma - Renhou Zhi; Fan Fan (Discover Oncology)
Abstract Purpose Solute carrier family 1 member 3(SLC1A3), a member of the glutamate transporter family, is implicated in the progression of gastric carcinoma and the renewal of thyroid carcinoma stem cells. The purpose of this work is to use experimental validation and bioinformatics analysis to look at the possible involvement of SLC1A3 in hepatocellular carcinoma (HCC). Materials and methods We examined the levels of SLC1A3 within HCC and its implications on immunological and epithelial–mesenchymal transition (EMT) features using the TCGA, ImmPort, and Molecular Signatures databases. The relationship between drug sensitivity and SLC1A3 expression was investigated using the GDSC database. Real-time quantitative polymerase chain reaction (qRT-PCR), Western blotting (WB), and cellular function assays were performed to assess SLC1A3 expression and its carcinogenic effects in HCC. Results According to our research, SLC1A3 overexpression in HCC is associated with a poor prognosis. Elevated levels of SLC1A3 promote HCC cell motility and invasion and can affect the prognosis of HCC by modifying immune responses and epithelial–mesenchymal transition. SLC1A3 has emerged as a novel prognostic marker in HCC and is associated with resistance to certain antitumor drugs. Conclusion SLC1A3 functions as a cancer-promoting factor contributing to poor HCC prognosis by affecting immune cell infiltration and regulating the EMT process. Elevated SLC1A3 expression may also serve as a predictor of treatment response to specific antitumor drugs.